Artificial Intelligence Tools in Developing English Writing Skills: Bangladeshi University EFL Students’ Perceptions - Khan, Afrida Lubaba; Hasan, Md Mahadhi; Islam, Md Nakibul; Uddin, Md Sharif (English Education: Jurnal Tadris Bahasa Inggris, 2024)
Artificial intelligence technologies are advancing rapidly, and this advancement has led to the infiltration of AI tools in various educational sectors worldwide, influencing teaching methodologies and learning experiences. Bangladeshi tertiary-level EFL students, due to the educational and technological landscape in Bangladesh, face unique challenges and diverse perceptions. This study aims to address the gap in factual investigations concerning the effectiveness and acceptance of AI tools among Bangladeshi tertiary-level EFL students. While previous studies focused on language learning at a general level, limited attention has been given to the usability of AI in improving writing skills, particularly in the Bangladeshi context. Therefore, this study explores Bangladeshi tertiary-level EFL students’ perceptions regarding the usage, challenges, and accessibility of AI tools in developing their writing skills. The study employs a mixed-method approach. Specifically, a sequential mixed method, combining both quantitative (survey with 70 participants) and qualitative (in-depth interviews with 10 participants) methods to comprehensively analyze students’ attitudes and experiences. The findings reveal that AI tools have various effects on students’ English writing skills, with strong support for AI as an invaluable educational resource. However, barriers such as technical issues, the potential for plagiarism, prevalent misconceptions, and the need for critical thinking skills were also identified. The study contributes to the ongoing discourse of AI integration in language learning, providing insights into how AI tools can complement, rather than replace, traditional learning methods.